2004
DOI: 10.1001/archsurg.139.12.1314
|View full text |Cite
|
Sign up to set email alerts
|

Infrascrotal, Perineal, Femorofemoral Bypass for Arterial Graft Infection at the Groin

Abstract: Hypothesis: Infrascrotal, perineal, femorofemoral bypass is an acceptable procedure for treating infection of a prosthetic arterial graft limited to a unilateral groin. Design: A consecutive sample clinical study with a mean follow-up of 29 months. Setting: The surgical department of an academic tertiary care center and an affiliated secondary care center. Patients: Nineteen patients with a mean age of 68 years with prosthetic graft infection at the outflow anastomosis on a femoral artery at the Scarpa triangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Daptomycin has also demonstrated interesting capacities in biofilm penetration [65], and some studies revealed a higher activity against stationary phase staphylococci than vancomycin [66]. However, the clinical relevance of all these in vitro data is still lacking and the therapeutic choice of the antimicrobial chemotherapy to use to treat Page 9 of 64 A c c e p t e d M a n u s c r i p t 9 PVGIs cannot be only based on such biofilm penetration criteria, highlighting that clinical studies and data are required.…”
Section: Choice Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daptomycin has also demonstrated interesting capacities in biofilm penetration [65], and some studies revealed a higher activity against stationary phase staphylococci than vancomycin [66]. However, the clinical relevance of all these in vitro data is still lacking and the therapeutic choice of the antimicrobial chemotherapy to use to treat Page 9 of 64 A c c e p t e d M a n u s c r i p t 9 PVGIs cannot be only based on such biofilm penetration criteria, highlighting that clinical studies and data are required.…”
Section: Choice Of Antibioticsmentioning
confidence: 99%
“…For other obligate anaerobes such as B. fragilis, the possibility of suppressive treatment should be evaluated after multidisciplinary consultation (C-III). weeks post-operatively [5,7,9,[11][12][13][14]25,27,28,35,37] without the risk of relapse appearing greater than that encountered when the treatment period is longer. This 6-…”
Section: For Suboptimal Surgical Treatmentmentioning
confidence: 99%
“…Johnson a rapporté un cas de pontage perméable après 7 ans de suivi [ 12 ]. Une seule étude dans la littérature s'est intéressée à la perméabilité de ce type de pontage, celle d'Illuminati et al colligeant 19 patients, avec une perméabilité primaire de 86% à 3 ans et un taux de sauvetage du membre de 91% [ 13 ]. Cette publication [ 13 ] est d'ailleurs la dernière dans la littérature se rapportant à cette technique de revascularisation.…”
Section: Discussionunclassified
“…In addition to an operative mortality rate of an average of 5% and a recurrence rate of sepsis between 7 and 12%, the percentage of limb amputation after a thrombosis occurs, is also significant in the short or medium term from the graft implantation (between 10 and 20% at 5 years). 12…”
Section: Discussionmentioning
confidence: 99%